Histopathological evaluation in experimental envenomation of dogs with Crotalus durissus terrificus Venom - Sangiorgio, F. [UNESP]; Sakate, M. [UNESP]; Nogueira, R. M. B.; Tostes, R. A. (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
The present work evaluated histopathological aspects in experimental envenomation of dogs with Crotalus durissus terrificus venom. Twenty-eight mixed breed adult dogs were divided into three groups of seven animals each: Group I only venom; Group II - venom + 50ml antiophidic serum + fluid therapy; Group III venom + 50ml antiophidic serum + fluid therapy + urine alkalization. Lyophilized venom of Crotalus durissus terrificus was reconstituted in saline solution and inoculated subcutaneously at the dose of 1mg/kg body weight. Three animals of each group were subjected to euthanasia, and their muscular tissue, brain, spleen, kidneys, heart, lungs, stomach, small and large intestines, and popliteal lymph node fragments were collected for histopathological evaluation. There was myonecrosis in the inoculated limb, renal tubular degeneration, lymphoid hyperplasia of spleen, and unspecific reactive hepatitis. These results show the antigenicity and action of the venom on the immune system.
Keywords: histopathology; Crotalus durissus terrificus; dogs; treatment; intoxication